2020
DOI: 10.1088/1361-6560/abbb73
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of energy deposition and DNA damage using TOPAS-nBio

Abstract: Purpose. Monte Carlo (MC) track structure codes are commonly used for predicting energy deposition and radiation-induced DNA damage at the nanometer scale. Various simulation parameters such as physics model, DNA model, and direct damage threshold have been developed. The differences in adopted parameters lead to disparity in calculation results, which requires quantitative evaluation. Methods. Three simulation configurations were implemented in TOPAS-nBio MC toolkit to investigate the impact of physics models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…MC calculated TG‐43 dosimetry parameters using new configurations were carried out in this study and compared with previously published data, thus validated the proposed MC model and provided a new TG‐43 dataset. Implemented in TOPAS, an easier‐to‐use application of Geant4 MC code for the medical physicist, this model can be easily utilized in further studies regarding MC calculations such as IMBT and microdosimetric studies (along with the TOPAS‐nBio extension) 29,30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MC calculated TG‐43 dosimetry parameters using new configurations were carried out in this study and compared with previously published data, thus validated the proposed MC model and provided a new TG‐43 dataset. Implemented in TOPAS, an easier‐to‐use application of Geant4 MC code for the medical physicist, this model can be easily utilized in further studies regarding MC calculations such as IMBT and microdosimetric studies (along with the TOPAS‐nBio extension) 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the TG-43 dosimetry parameters for Varian Gam- microdosimetric studies (along with the TOPAS-nBio extension). 29,30 The deviation between calculations could be attributed to different source spectra and cross sections. A previous research 31 indicated that different 192 Ir source spectra can cause S k differences up to 2%.…”
Section: Discussionmentioning
confidence: 99%
“…Although probabilistic scenarios may be estimated for an individual’s radiation exposure on a mission (for example, with Monte Carlo methodology), true physiological consequences remain ultimately unknown, especially combined with other effects from phenomena like microgravity and isolated environments ( 143 ). Without a comprehensive understanding of the phenotypic response of Homo sapiens to space radiation, a genotypic solution may misidentify or omit essential or corollary transcription pathways.…”
Section: Discussion: Alternatives To Genetic Alteration and Modelingmentioning
confidence: 99%
“…The ionization energy of liquid water was set at 12.6 eV 20 and any interaction depositing energy equal to or greater than that value was assumed to cause ionization, with any excess energy transferred to the free radicals as kinetic energy. The DNA damage threshold was taken as 17.5 eV 21 and if a free radical kinetic energy was greater than or equal to this value, an indirect SSB was assumed. If any two indirect SSB occurred within 3.4 nm of each other (the average separation of 10 DNA base pairs) this was classified as an indirect DSB 22 .…”
Section: Methodsmentioning
confidence: 99%